Level of acuity, severity and intensity of care of adults and older adults admitted to the Intensive Care Unit - Renata Eloah de Lucena Ferretti-Rebustini; Nilmar da Silva Bispo; Winnie da Silva Alves; Thiago Negreiro Dias; Cristiane Moretto Santoro; Katia Grillo Padilha (SciELO, 2019)
ABSTRACT Objective: To characterize the level of acuity, severity and intensity of care of adults and older adults admitted to Intensive Care Units and to identify the predictors of severity with their respective predictive capacity according to the age group. Method: A retrospective cohort based on the analysis of medical records of individuals admitted to eight adult intensive care units in the city of São Paulo. The clinical characteristics at admission in relation to severity profile and intensity of care were analyzed through association and correlation tests. The predictors were identified by linear regression and the predictive capacity through the ROC curve. Results: Of the 781 cases (41.1% from older adults), 56.2% were males with a mean age of 54.1 ± 17.3 years. The burden of the disease, the organic dysfunction and the number of devices were the predictors associated with greater severity among adults and older adults, in which the organic dysfunction had the highest predictive capacity (80%) in both groups. Conclusion: Adults and older adults presented a similar profile of severity and intensity of care in admission to the Intensive Care Unit. Organic dysfunction was the factor with the best ability to predict severity in adults and older adults.